Unnecessary Items, Waste Issue and Solidarity Practices among Russian Consumers - Shabanova, Marina (Journal of Economic Sociology, 2024)
Drawing on the results of three all-Russia representative surveys (2017, 2020, and December 2022, N = 2000 in each case), this study for the first time reveals the data on the level, dynamics and factors related to how Russians engage in various practices of handling underutilized items that have not lost their consumer properties, but no longer needed by their owners. Special emphasis is made on solidarity practices, such as free transfer of such items to strangers and acquaintances (with the exception of relatives) as compared to market practices (sales through Internet platforms, second-hand shops, etc.) and disposing of items in the landfill. The results demonstrate that Russians with different values, socio-demographic and status characteristics exhibit different probability to engage in these practices. Young people (18-34) are a problematic group since they tend to throw items away and engage in market practices rather than in charitable giving. It has been shown that donors’ resource potential (willingness to transfer unwanted items in good condition to other people for free) has substantially declined in 2022 as compared to 2020. However, the donors’ potential has not been fully realized and it still remains fairly significant. Recommendations are made for measures to enhance the role of civil society and productive practices, while reducing the destructive ones in this sphere. The conclusion is made that the practices of discarding unnecessary items are increasingly becoming a tool for manifesting civic responsibility and expanding the boundaries of civil society in Russia.